An outdoor fibre bragg grating temperature sensor - Daud, Suzairi (2010)
A prototype outdoor fibre Bragg grating (FBG) temperature sensing system based on a commercial FBG has been designed, constructed, developed, and its performance evaluated. The commercial FBG sensor head has a center wavelength of 1553.865 nm, 0.24 nm bandwidth, >97 % reflectivity, and a length of (3.0+0.1) cm. In order to reduce the optical losses of the FBG system, the shortest optical fibre path used was (55.0+0.1) m. The temperature sensitivity of the system was evaluated for different placement heights from the rooftop floor with and without the presence of focusing elements. The TLS was used to provide the broadband light source via a fibre optic cable of wavelength 1550 nm. The OSA was used to display the transmission and reflection spectrum from which the Bragg wavelength, XB, bandwidth, and power dip are obtained. The transmission spectrum was obtained through direct connection to the FBG and the reflection spectrum using a (2x2) 3dB coupler. The Bragg wavelength change with temperature changes was used to determine the FBG system’s performance. Results obtained shows that AXB is directly proportional to temperature changes for both transmission and reflection spectrum with and without focusing elements at different placement heights. The gradient of AXB versus temperature provides the sensitivity of the FBG system. The average sensitivity of the FBG sensor system measured was 10.0 pm/°C without any focusing element. It has an average of 12.5 pm/°C when the FBG sensor head was focused with a convex lens and 13.9 pm/°C when focused with a hand lens. The FBG sensor system sensitivity was increased when a hand lens was used. The sensitivity is constant irrespective of the FBG sensor head position from the floor. Thus, a prototype FBG sensing system has been developed for outdoor temperature measurements.